PENERAPAN TEORI I.A. RICHARDS PADA PUISI “LAGU RINDU” KARYA HERI ISNAINI - elis supriati (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
This article describes the application of I.A. Richards theory in the poem "Lagu Rindu" by Heri Isnaini. The use of this theory includes the application of physical elements and inner elements to poetry. These elements define a poem into a whole work. Poetry analysis in this article will discuss and explain the structure of poetry consisting of typography, verse, array, diction, and majas. Meanwhile, the inner elements discussed include themes, tones, feelings, and mandates. The application of I.A. Richards theory shows that the poem "Lagu Rindu" by Heri Isnaini has strong elements that build poetry as a whole and meaningful. Thus, this research resulted in a comprehensive discussion of poetry so that poetry can be understood from the physical and inner elements in accordance with the application of the theory of I.A. Richards. In addition, the application of this theory shows a deep meaning in poetry and its relation to other texts so that poetry can give good effect and character formation and learning experience.